As liberdades individuais no contexto da sociedade biotecnológica: o princípio da autonomia em relação a terminalidade da vida - Forest, Rosane (Universidade do Vale do Rio dos Sinos, 2014)
The last few decades have been marked by increasing technological advances in virtually all sectors of society, however, with regard to life in its broadest sense, the greatest achievements can be observed in the medical field. Biotechnology deserves special attention because of the power it exerts over human life from conception until after death. In this context, the limitations of the legal system emerge as the law is not able to answer the flood of questions produced by modern medical practice and its power to interfere in the natural course of life and death process. This thesis aims to present a reflection on the right to life and the right to health - read in its broadest conception - and set them in the midst of contemporary society, translated as a biotech company and paradoxical, since while in which values human essence, seeks to fill the technology limitations and typically human imperfections. The study aims to treat the terminally life, touching dignified death, based on the principle of autonomy, in matters which relate to the life-prolonging therapies in patients beyond the expectation of cure. The reference base is confirmed by the fundamental rights and principles, however, the survey will transdisciplinary way, using authors who reflect on the issue of life and law from the perspective of bioethics, sociology and philosophy. Worth mentioning that the dignified death treated herein shall solely in the realm of prolonging life issues in medically ill considered outside the expectation of cure, any other use of the institute, will not be subject of the study in question, which also does not net you the discussions of a religious nature. Although relevant comparative analysis on the conduct of the subject countries in North America, Europe and South America, the theme will be developed from the perspective of Brazilian law.
Keywords: Biotechnology; Autonomy; Dignified death; Right to life; Biotecnologia; Autonomia; Morte digna; Direito à vida; ACCNPQ::Ciências Sociais Aplicadas::Direito